The Effect of Diet Hypertension on the Event of Hypertension in the Elderly - Musta'in Musta'in; Carlos Filipe da Costa Nunes; Tri Yuniarti; Lestari Eko Darwati (Global Health Science Group, 2022)
Hypertension diet is one way to treat hypertension without serious effects, because of its natural control method. It's just that many people consider a hypertension diet to be troublesome and unpleasant (Purwati, 1997). Hypertension is a condition where the systolic blood pressure exceeds 140 mmHg and diastolic exceeds 90 mmHg, the normal number of blood pressure is systolic pressure 120 mmHg and diastolic 80 mmHg occurs at the age < 60 years. In the elderly population, hypertension is defined as a systolic pressure of 160 mmHg and a diastolic pressure of 90 mmHg. Currently, the mortality rate due to hypertension in Indonesia is very high. The prevalence rate of hypertension in Indonesia based on riskesdas (basic health research) 2018 reached 34.1 percent of the population. Hypertension is divided into 2, namely essential hypertension and secondary hypertension. The cause of hypertension in the elderly is due to changes in the valve; the heart valves thicken and become stiff, the heart's ability to pump blood decreases by 1% every year after the age of 20, so contractions and volume also decrease. Clinical manifestations of hypertensive patients include: Complaining of headache, dizziness, weakness, fatigue, restlessness, nausea and vomiting, epistaxis, decreased consciousness. Supporting examinations for hypertension include: laboratory examination, CT Scan, ECG, IUP, and chest photo. The purpose of this study was to determine the effect of dietary hypertension on the incidence of hypertension in the elderly in Manang Village, Grogol District, Sukoharjo Regency. This study used a cross-sectional study design. The sample of this study amounted to 30 elderly people. The instrument of this study used a questionnaire and measurement of hypertension using a sphygmomanometer and a stethoscope. The analytical method used is Person Chisquare. with a p value of 0.001 p < 0.05, with a Prevalence Ratio (PR) of 8.250. there is a significant effect between diet hypertension and The incidence of hypertension in the elderly in Manang Village, Grogol District, Sukoharjo Regency. where a good hypertension diet increased 8,250 times the bad hypertension diet compared to hypertension.